2021
DOI: 10.5009/gnl210362
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota and Genetic Susceptibility in the Pathogenesis of Pancreatitis

Abstract: Pancreatitis is one of the most common inflammatory diseases of the pancreas caused by autodigestion induced by excessive premature protease activation. However, recognition of novel pathophysiological mechanisms remains a still challenge. Both genetic and environmental factors contribute to the pathogenesis of pancreatitis, and the gut microbiota is a potential source of an environmental effect. In recent years, several new frontiers in gut microbiota and genetic risk assessment research have emerged and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Studies have shown that mutation of the transmembrane conductance regulator of cystic brosis (CFTR) and tumour necrosis factor-promoting polymorphism may contribute to the onset of HTG-AP. More research is necessary to examine the speci c role of genetic factors in HTG-AP development [32]. HTG-AP can cause and worsen AP through various pathways, and it has been demonstrated that HTG-AP is generally associated with higher clinical severity and complication rates [9,33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mutation of the transmembrane conductance regulator of cystic brosis (CFTR) and tumour necrosis factor-promoting polymorphism may contribute to the onset of HTG-AP. More research is necessary to examine the speci c role of genetic factors in HTG-AP development [32]. HTG-AP can cause and worsen AP through various pathways, and it has been demonstrated that HTG-AP is generally associated with higher clinical severity and complication rates [9,33].…”
Section: Discussionmentioning
confidence: 99%
“…The knockout of the receptor GPR43 increased susceptibility to dextran-sodium-sulfate-induced colitis in mice by increasing chemotaxis of neutrophils and inflammatory gene expression [ 4 ]. SCFAs are considered to be vital components in maintaining the integrity of the intestinal barrier [ 23 ]. Studies have shown that SCFAs can promote the intestinal epithelial thigh junction protein synthesis, inhibit intestinal permeability, and even enhance the intestinal mucosal immune barrier function [ 24 ].…”
Section: Gut Microbiota Profile In Pancreatitismentioning
confidence: 99%
“…Increased intestinal permeability has been demonstrated in a significant percentage of patients with AP [120], with circulating bacterial DNA representative of gut bacteria in 68.8% of patients with AP. Zhang and colleagues showed that patients with AP had more Proteobacteria and Bacteroidetes and fewer Actinobacteria and Firmicutes in their feces, compared with normal controls [121]. The clinical significance of gut dysbiosis is poorly understood, but these patients have been found to have worse outcomes .…”
Section: Gut Microbiome Impact In Apmentioning
confidence: 99%